Optimisation of parameters affecting the performance of single compartment CEDI unit - Thorat, Prathamesh P.; Desale, G. R.; Gajjal, S. Y.; Patil, Sagar R. (1ST International Conference on Computing Communication Control and Automation ICCUBEA 2015, 2015)
The present work describes the production of the ultrapure water using Continuous Electro-deionization (CEDI) method. TheCEDI unit consist of ion exchange membranes, Mixed Bed-12 (MB-12) ion exchange resin and electrodes to remove ion impurities from feed water. The product water from the RO unit is supplied to the CEDI unit. The Quality of the ultra-pure water is determined by the amount of ions present in the water. Higher quality of Ultra-pure water is obtained when the maximum number of ions is transferred through the membranes. The Parameters affecting the performance of the CEDI unit are identified and optimized for maximum ions exchange. Inorder to reduce the number of experimentsTaguchi method was used for optimisation of operating parameters. An orthogonal L array (three factor and three level) was employed to evaluate the effect of feed concentration (35,40and 45 ppm), Flow rate (8, 9 and 10 LPH) and voltage (22, 23, 24 volts). Thus it was observed that increasing the applied voltage anddecreasing the waterflow rateincreases the number of ions transfers through the membrane. However, decreasing water flow rate has certain limits as it decreases the production capacity of the unit. Also it is observed that decreasing the ions in the feed water decreases the overall transfer of ions.
Keywords: Continuous Electro-deionization; Ion Exchange membranes; Optimisation; Taguchi method; Ultrapure Water